Examining the Relationship between Math Self‐Efficacy and Statistics Motivation in the Introductory Business Statistics Course: Self‐Compassion as a Mediator. (25th March 2018) - Ramos Salazar, Leslie
ABSTRACT: Because business statistics students often experience a lack of statistical motivation, business educators need to understand the factors that influence students' motivation levels in undergraduate‐level business statistics courses. The purpose of this study was to examine the role of math self‐efficacy and self‐compassion on students' motivation levels and the gender differences among the main variables. The regression results showed that math self‐efficacy was a positive predictor of statistics motivation. Self‐compassion was also found to be a partial mediator of the relationship between math self‐efficacy and statistics motivation. Gender differences were also found in business students' math self‐efficacy, self‐compassion, and statistics motivation.